A flexible ultra-robust ZnO-AgNWs/PDMS-based hybrid nanogenerator for simultaneous energy harvesting and sensing applications; Sensors and Actuators A: Physical; Vol. 384 - Chen Wei; Zhao Sheng-Zhe; Xiang Guo-Tao; Lu Ran; Xu Jia-Lei; Rodriguez (Rodriges) Contreras R. D. Raul David; Sheremet E. S. Evgeniya Sergeevna; Hu Yong-Da; Chen Jin-Ju (2025, 2025)
Title screen